Possible Ways of Solving the Problem of Prison Overcrowding in the Republic of Serbia - Ilić, Aleksandra (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
The author analyzes the ways in which it is possible to solve the problem of overpopulated prisons in Serbia. The problem of overpopulation can be influenced on the one hand by reducing the number of prisoners, both those for whom the measure of detention is pronounced and those who were sentenced to unconditional imprisonment. The number of detainees can be reduced by using other measures to a greater extent to ensure the presence of the defendant. The number of prison sentences could be reduced by pronouncing, where possible, alternative sentencing. On the other hand, the problem of overpopulation can be affected by the increase in accommodation facilities, as well as by improving living conditions in prisons. In this sense, the author discusses the importance of building private prisons. Finally, it is mentioned that there are other possible ways of solving the problem of overcrowded prisons, such as improving the professional capacity in prisons. Particularly, it is stressed that the importance of training judges and prosecutors on the new solutions in this area, which will certainly affect the resolution of the problem of overcrowded prisons.